Islamic-based hierarchical consumption: guide for Muslim consumer / Basri Abd Ghani, Noraini Ismail and Nor Azira Mohd Radzi - Abd Ghani, Basri; Ismail, Noraini; Mohd Radzi, Nor Azira (Universiti Teknologi MARA, Perlis, 2019)
Aspects of consumption are becoming increasingly important as the current approach fails to solve many collective socio-economic phenomena that lead to poverty, hunger and unemployment. There is no doubt that the current approach is either in the form of concepts, principles, theories or models that have been used to analyse and understand the discipline of consumption in theory and practice. However, the current approach which is based on ‘tasawwur’ and Western epistemology are not suitable to be applied to the culture of the East, especially the Muslim community because of the differences in background beliefs, culture and environment. This reality highlighted the importance of Islamic approach. However, the existing of Islamic approach is smaller compared to its conventional counterparts. It justifies building a new approach that reflects on ‘tasawwur’, epistemology and the ontology of Islam.